2012
DOI: 10.1111/j.1551-2916.2012.05173.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FeOt Content and CaO/SiO2 Ratio on Hydrogen Dissolution in CaF2CaOSiO2‐Based Welding Fluxes

Abstract: The solubility of hydrogen in the CaF2–CaO–SiO2–FeOt slag system was studied to characterize the dependence of hydrogen dissolution behavior on the CaO/SiO2 ratio and the Fe3+/Fe2+ redox equilibrium at 1823 K. In an acidic slag composition, the dissolved hydrogen seems to exist as an incorporated hydroxyl, where the supplied water vapor reacts with the bridged oxygen (Oo) of the slag network. In a basic slag composition, hydrogen dissolves as a free hydroxyl in the molten slag by reacting with the free oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…With the ability to distort the dipole moment in a molecule, IR induces certain molecular vibrations (IR vibrational modes) that are characteristic of the chemical environment of the molecule (fingerprint). FTIR has been used to qualitatively determine the structure of silicate melts by many researchers . For qualitative/semiquantitaive determination of silicate species in the melt, a careful peak deconvolution should be done, vide infra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the ability to distort the dipole moment in a molecule, IR induces certain molecular vibrations (IR vibrational modes) that are characteristic of the chemical environment of the molecule (fingerprint). FTIR has been used to qualitatively determine the structure of silicate melts by many researchers . For qualitative/semiquantitaive determination of silicate species in the melt, a careful peak deconvolution should be done, vide infra.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR has been used to qualitatively determine the structure of silicate melts by many researchers. [48,50] For qualitative/semiquantitaive determination of silicate species in the melt, a careful peak deconvolution should be done, vide infra. Infrared spectra were collected with a Continuum IR Microscope coupled to a Nicolet 6700 FTIR Spectrometer supplied by Thermo Scientific (Waltham, MA).…”
Section: Ftir-ras Spectroscopymentioning
confidence: 99%
“…In that research, it was revealed that the excess free energy of oxides in slag (CaO, MgO, MnO) is strongly dependent on the abundance of silicon anionic units, which was also elucidated further with ionization potential (Z/r 2 ) of the metal ions. In another study, Park et al [32] reported an increase of depolymerization of the CaF 2 -CaO-SiO 2 -FeO x slag system with increasing FeO x (0 to 21.5 wt.%). In this basic slag, FeO x acted as a polymerizing agent of the silicate slag.…”
Section: Previous Studies On Structures Of Copper-making Slagsmentioning
confidence: 92%
“…Research has shown that light weight high strength steels such as high Mn containing AHSS steel (advanced high steel strength) are especially prone to defects during the welding process. According to Park et al, [1][2][3][4][5] dilution of the weld pool by the base plate, contamination of the weld pool by exogenous gases and particles, and the transfer of elements from slags are some of the issues observed during the welding process, which can exacerbate cracking in the weld zone. In particular, the viscous properties of the welding flux and its optimization ensure discrete separation of the metal from the slag, minimization of gas bubble entrainment, and improved spreading characteristics to inhibit atmospheric contamination.…”
Section: Introductionmentioning
confidence: 99%